Born to the saddle - Beaudine, William, 1892-1970; Erickson, Leif, 1911-1986; Young, Gordon, 1886-1948.; Elliott-Shelton Films, Inc.; Cinetel Films ([Los Angeles, CA] : Elliott-Shelton Films Inc., 1953)
Bent on revenge for the death of his father and the theft of their ranch, young Bill Walton rides into town seeking the aid of his uncle. As he rides into town, he takes a bullet meant for gambler Matt Daggett and across the street lies his uncle, victim of the gambler's gun. Dagget looks on Bill as 'good luck' and nurses him back to health and gives him the job of training "Blue Chip", the fastest quarter horse in the west, for a big race. Bill doesn't know that Dagget plans to fix the race and put his own money on another horse. --
Adapted from the novel: Quarter horse / by Gordon Young.
Leif Erickson, Donald Woods, Rand Brooks, Chuck Courtney.
Cinematographer, Marcel Le Picard; editor, Chester W. Schaeffer; music, Emil Velazco.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Teenagers -- Drama; Race horses -- Drama; Cowboys -- Drama; Western films; Feature films; Internet videos; Streaming video